Trafford Whitelock interviewed by Amy McGrath - Whitelock, Trafford, 1916-1998.; McGrath, Amy, 1921-2019 (1981)
Trafford Whitelock, radio producer for the BBC, playwright and theatre critic, talks on movies in the late 1920's; various actors and actresses; Gloria Swanson; combined movies and live performers; Queenie Paul and Mike Connors; his work as a writer and producer; the Sydney theatre scene in the mid 30's; the First Australian Ballet Company; Louise Lightfoot and Misha Berlekov (Burlakov).
Recorded on 11 June 1981.
Also available online
Trafford Whitelock established his career as a radio producer for the BBC since 1951 following a radio career with the Australian Broadcasting Commission and the Macquarie Broadcasting Commission. He developed a reputation as a keen arts critic particularly of theatre and ballet. He also wrote plays for the theatre.
Timed summary (5 p.) and uncorrected transcript (typescript, 16 leaves).
Keywords: Whitelock, Trafford, -- 1916-1998 -- Interviews; Swanson, Gloria, -- 1899-1983 -- Anecdotes; Paul, Queenie -- Anecdotes; Connors, Mike -- Anecdotes; Lightfoot, Louise, -- 1902-1979 -- Anecdotes; Burlakov, Mischa, -- approximately 1884-1965 -- Anecdotes; First Australian Ballet -- History; Dramatists, Australian -- Interviews; Radio producers and directors -- Australia -- Interviews; Theater -- New South Wales -- Sydney -- History -- 20th century; Ballet -- Australia -- History; Motion pictures -- History -- 20th century